CONSIDERATION OF THE JUDGE DECISION, CASE NUMBER:373/PID.B/2020/PN.PDG CONCERNING FORCED DEFENSE VIEWED FROM THE ASPECT OF JUSTICE - Gadi, Dionisius Pani; Soerodjo, Irawan (Jurnal Independent, 2023)
Perpetrators of Persecution Causing Death Are A Criminal Act As Stipulated In The Statutory Regulations. In writing, the author conducts research regarding a decision, namely Decision Number 373/Pid.B/2020/PN.Pdg where this decision has caused the death of the victim which was carried out by a security guard at Teluk Bayur Padang Port. This act was triggered by an attack that was previously carried out by the victim against the witness and the defendant,resulting in a forced defense that exceeded the limit or noodweer excess due to severe mental turmoil as stipulated in Article 49 paragraph (2) of the Criminal Code. The formulation of the problems discussed in this thesis are: 1) How is the judge, s consideration of the criminal act of persecution resulting in death due to forced defense that exceeds the limit (Noodweer Exces) based on Decision No. 373/Pid.B/2020/PN.Pdg? 2) How is the application of Article 49 paragraph (2) of the Criminal Code as an Excuse in criminal liability in Decision No.373/Pid.B/2020/PN.Pdg The research method used by the author is a normative juridical method. From the results of this study, the authors draw conclusions 1) The Basis for Considerations of Judges in Deciding Cases for the Crime of Persecution which causes death is not in accordance with the Laws and Regulations in Decision Number: 373/Pid.B/2020/PN Pdg based on 2 (two) types of considerations, namely juridical considerations and non-juridical considerations. Juridical considerations are judges; considerations based on the factors revealed in the trial and by law have been determined as matters that must be included in the trial. Non- juridical considerations are circumstances related to the defendant himself such as the defendant background in committing a crime, the impact of the defendants actions, and the defendant’s condition. In imposing criminal sanctions in cases of maltreatment that causes death not in accordance with statutory regulations, judges should pay more attention to andconsider the applicable statutory provisions by taking into account the condition of the accused and applying Article 49 paragraph (2) of the Criminal Code in that case. 2) The application of Article 49 paragraph (2) of the Criminal Code as a reason for forgiveness in criminal liability in decision Number 373/Pid.B/2020/PN.Pdg can be said to not exist, even though the defendant committed the crime because he felt his life was threatened which resulted in the defendant’ s condition was messed up so he committed the crime.Keywords: Reasons For Forgiveness, Noodweer Excess, Persecution Causing Death